Improving the Quality of Children's Worship Through the Dawn Prayer Education Program at the TPQ of the Ikhwanul Muslimin Mosque - Junaidi Marbun; Martin Kustati; Nana Sepriyanti (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
As the foundation for the nation's successor, it should provide a solid apprenticeship for children, so that they can live life as well as possible, especially in treatment and worship. Worship education is the most important thing to be introduced early on to children, so that they get used to and understand that worship is the obligation of a Muslim. The purpose of this study is to analyze worship education carried out through the dawn education program at the Ikhwanul Muslimin Mosque TPQ. The research method used in this research is qualitative which describes the phenomena that occur and is described through narratives or sentences, and the approach used is a case study with data collection techniques through observation, interviews and documentation and analyzed by data collection, data reduction and conclusion drawing. The results of this study indicate that there is an increase in the quality of worship, the formation of a disciplined character, an increase in spiritual understanding. Therefore, the contribution of this research is strengthened by planting and implementing worship education through religious programs to improve the quality and religious values in children, so that they can become the nation's successors who obey religious values and adhere to religious concepts.